PHILOSOPHICAL AND THEORETICAL TEACHING OF AMIR KHUSRAV DEHLAVI (Scientific journal of the Fergana State University, 2024)
The article presents the philosophical and theoretical ideas and poems of the great Indian philosopher and poet, thinker Amir Khusrav Dehlevi, his arts, works, manuscripts and views on the emergence of art. Philosophical and artistic paintings of the thinker Amir Khusrav Dehlevi are on view.